Perbedaan Hasil Belajar IPS Antara Siswa Menggunakan Metode Pembelajaran Group Investigation Dengan Metode Pembelajaran Turnamen Game Tim - Suhirman Suhirman (Indonesian Journal of Social Science Education (IJSSE), 2023)
The purpose of this study was to find out the differences in social science learning outcomes between students who were taught using the Group Investigation learning method using the Team Game Tournament learning method. This study uses a quasi-experimental design non-equivalent control group design. The population of this research is the 5th grade students of Elementary School 20. The sampling technique used is the cluster technique, namely students in grades 5 a and b of Elementary School 20 Bengkulu City. Grade 5a students are taught using the Group Investigation cooperative learning method, and grade 5b students are taught using the Team Game Tournament learning method. The results showed that there was a significant difference in social science learning outcomes between those taught using the Group Investigation learning method and students taught using the Team Game Tournament learning method, obtained a statistical value of F = 12.71 with a significance value of 0.001.